Speaking of sexuality - Moore, Nelwyn B.; Davindson, J. Kenneth (Los Angeles : Roxbury Publishing Company, 2001)
Contenido: The authors delineate the reasons for the emergence of two sexual revolutions in the late twentieth century and propose a pluralistic approach to sexuality: individual choices guided by the values of honesty, equality and responsibility.